An Actuarial Comparison of General Business Insurance Loss Reserving: Evidence from Classical Chain Ladder and Cape-Cod Technical Provisions Numerical Techniques - Ogungbenle, Gbenga Michael; Phulara, Keshab Raj (Nepal Journal of Mathematical Sciences, 2023)
The assets and liabilities of a general insurance underwriter constitutes two main variables usually adopted when evaluating the solvency requirements of a general insurance firm under which technical provisions form an unprecedented part of insurance liabilities. The technical provision of a general insurance business comprises provisions for unearned premiums and provisions for claims. The technical provisions specified under solvency II requirements asserts that the classical actuarial techniques for evaluating the best estimate for provisions in general business insurance obligations contains the run off triangles. The objective of this study are to (i) estimate the chain ladder reserve (ii) estimate the cape-cod reserve and (iii) compare the chain ladder with the cape-cod mathematical techniques with the disposition of estimating losses and technical provisions. These techniques evaluated through some run-off triangles can be adopted to estimate technical provisions for the outstanding claims. Computational evidence from our results over the periods considered revealed that despite the fact that the cape-cod technique is a mathematical variant of the chain ladder technique which seems less dependent on the variations of a single observation, the chain ladder reserve is numerically less than the corresponding cape-cod reserve and hence CLRESERVE = 18534.42 < CCRESERVE = 19123.84